Governance Mechanism and Financial Reporting Timeliness of Listed Firms on The Nigeria Stock Exchange (Journal of Entrepreneurship and Business, 2021)
The issue of financial reporting timeliness is central to quality of financial report and equally influence the decisions of investors on were to commit their resources. While there is a regulatory requirement on when financial reports should be made available, it appears that firms have continued to flout the requirements of the regulations. Considering the fact that investors eagerly anticipate the release of financial report to invest in a firm, a delay in such report could lead to investment in an alternate firm. It is against this back drop that this study examines the effect of corporate governance mechanisms on financial reporting timeliness of listed firms in Nigeria. The study used a sample of 65 firms out of the total population of listed firms on the Nigeria stock exchange. The study analyzed the data collected using descriptive statistics, correlation analysis and the hypotheses were tested using Poisson regression analysis technique. First, it was found that it takes an average of three months after 31st December for financial statement to be reported. The study found that for all the firms combined, board independence, and managerial shareholding significantly reduces the number of days it takes for financial report to be reported. Also, board size and board independence decrease financial reporting lag but without statistical significance. On the other hand, the signs of the variables change when individual sectors are considered. For the market as a whole, it is recommended that the Securities and Exchange Commission should continue to enforce compliance with governance mechanisms as to aid reporting timeliness which provide basis for investors to make their investment decision timely as well in the market. On a specific note, firms in the industrial goods, conglomerate, banking sector and consumer goods sector should be given a closer monitor by the SEC since most of the governance variables rather increases the delay. To the aforementioned, it is recommended that the boards should be made more effective. The effectiveness of the board should be improved in terms of capability of the board members and since the relationship between board size and reporting timeliness is a direct one (moving in the same direction) management of these sectors should equally consider reducing its board size since a decrease in board size will decrease the number of days it takes for financial report to be filed. This is necessary because large size can lead to a lot of debate which could take time before an issue is addressed.
Keywords: Array; Array; Array